Analysis and Implementation of Multiple-Input, Multiple-Output VBLAST Receiver From Area and Power Efficiency Perspective - Khan, Z.; Arslan, T.; Thompson, J.S.; Erdogan, A.T. (IEEE transactions on very large scale integration (VLSI) systems, 2006)
This paper presents an analysis of the vertical Bell Laboratories layered space time (VBLAST) receiver used in a multiple-input multiple-output (MIMO) wireless system from the hardware implementation perspective and identifies those processing elements that consume more area and power due to complex signal processing. This paper models a scalable VBLAST receiver based on minimum mean square error (MMSE) nulling criteria assuming a block flat fading channel. After identifying the major area and power consuming blocks, this paper proposes two area and power efficient VLSI architectures for the block that computes pseudoinverse of the channel matrix. This paper discusses different tradeoff issues in both architectures and compares them with the architectures in the literature